Gut microbiota and renin-angiotensin system: a complex interplay at local and systemic levels - Jaworska, Kinga; Koper, Mateusz; Ufnal, Marcin (American journal of physiology: Gastrointestinal and liver physiology, 2021)
Gut microbiota is a potent biological modulator of many physiological and pathological states. The renin-angiotensin system (RAS), including the local gastrointestinal RAS (GI RAS), emerges as a potential mediator of microbiota-related effects. The RAS is involved in cardiovascular system homeostasis, water-electrolyte balance, intestinal absorption, glycemic control, inflammation, carcinogenesis, and aging-related processes. Ample evidence suggests a bidirectional interaction between the microbiome and RAS. On the one hand, gut bacteria and their metabolites may modulate GI and systemic RAS. On the other hand, changes in the intestinal habitat caused by alterations in RAS may shape microbiota metabolic activity and composition. Notably, the pharmacodynamic effects of the RAS-targeted therapies may be in part mediated by the intestinal RAS and changes in the microbiome. This review summarizes studies on gut microbiota and RAS physiology. Expanding the research on this topic may lay the foundation for new therapeutic paradigms in gastrointestinal diseases and multiple systemic disorders.